Mineralization- and remodeling-unrelated improvement of the post-yield properties of rat cortical bone by high doses of olpadronate - Capozza, Ricardo Francisco (2013)
Some pharmacologic effects on bone modeling may not be evident in studies of remodeling skeletons. This study analyzes some effects of olpadronate on cortical bone modeling and post-yield properties in femurs diaphyses (virtually only-modeling bones) of young rats by mid-diaphyseal pQCT scans and bending tests. We studied 20/22 male/female animals traetad orally with olpadronate (45-90 mg/kg/d, 3 months) and 8/9 untreated controls. Both OPD doses enhanced diaphyseal cross-sectional moments of inertia (CSMI) with no change in cortical vBMD and elastic modulus. Yield stiffness and strength were mildly increased. Postyield strength, deflection and energy absorption were strikingly enhanced. Ultimate strength was enhanced mainly because of effects on bone mass/geometry and post-yield properties. The large improvement of post-yield properties could be explained by improvements in bone geometry. Improvements in bone mass/geometry over weight-bearing needs suggest an enhanced modeling-related response to mechanical stimuli. Effects on tissue microstructural factors (not measured) could not be excluded. Results reveal novel olpadronate effects on bone strength and toughness unrelated to tissue mineralization and stiffness, even at high doses. Further studies could establish whether this could also occur in modeling-remodeling skeletons. If so, they could counteract the negative impact of anti-remodeling effects of bisphosphonates on bone strength.